Effect of Antioxidants on the Gut Microbiome Profile and Brain Functions: A Review of Randomized Controlled Trial Studies - Aleksandra Hyży; Hanna Rozenek; Ewa Gondek; Mariusz Jaworski (Foods)
Background: Antioxidants are widely recognized for their potential health benefits, including their impact on cognitive function and gut microbiome modulation. Understanding these effects is essential for exploring their broader clinical applications. Objectives: This review aims to evaluate the effects of antioxidants on the gut microbiome and cognitive function, with a focus on findings from randomized controlled trials (RCTs). Methods: The studies involved human participants across a range of age groups, with interventions encompassing natural antioxidant sources, such as berries, as well as specific antioxidant vitamins. An extensive search across PubMed, SCOPUS, and Web of Science databases identified six relevant RCTs, each evaluated for potential bias. Results: These studies focused on a variety of antioxidant-rich products, including both naturally derived sources and supplemental forms. Antioxidants, including vitamins C, B2, and D, along with polyphenols such as xanthohumol, fermented papaya, peanuts, and berry extracts, demonstrate the potential to support cognitive function and promote gut health through mechanisms that modulate microbiome diversity and reduce inflammation. However, observed changes in microbiome diversity were modest and inconsistent across the studies. Conclusions: While preliminary evidence suggests that antioxidants may benefit gut health and cognitive function, the heterogeneity of existing studies limits their immediate clinical applicability. Additionally, more robust RCTs are needed to substantiate these findings and guide future interventions.